Influence of Quartz Fiber on Electromagnetic Wave Transmission Properties of High-Alumina Cement Paste - Yang, Bin; Li, Yue; Liu, Jianglin; Li, YiNuo; Jin, Caiyun; Li, Hongwen (Frontiers in Materials, 2022)
In this paper, the effects of quartz fibers on the resistivity, complex permittivity, complex permeability and S-parameters of high-alumina cement pastes are investigated. Meanwhile, the change of microstructure after adding quartz fibers were analyzed by mercury intrusion porosimetry (MIP) and scanning electron microscope (SEM). The results show that with the increase the content of quartz fiber, the real part of complex permittivity decreases, while the imaginary part of complex permittivity, dielectric loss tangent and resistivity increased. At the same time, there are more small pores, and the interface situation is more complicated after adding quartz fiber. Therefore, the reflectivity decreases and the absorptivity increases, but the scope of increase in the absorptivity is smaller than the decrease in the reflectivity, resulting in an increase in the transmittivity. When the content of quartz fiber is 0.15%, 0.30%, 0.45% and 0.60%, the average transmittance of high-alumina cement paste is increased by 3.69%, 6.18%, 15.51% and 21.03% respectively. It is indicated that the quartz fibers can improve the wave transmission properties of the high-alumina cement paste.